2021
DOI: 10.1111/brv.12803
|View full text |Cite
|
Sign up to set email alerts
|

Seawater intrusion: an appraisal of taxa at most risk and safe salinity levels

Abstract: Seawater intrusion into low‐lying coastal ecosystems carries environmental risks. Salinity levels at these coastal ecosystems may vary substantially, causing ecological effects from mortality to several sublethal endpoints, such as depression of rates of feeding, somatic growth, or reproduction. This review attempts to establish safe salinity levels for both terrestrial and freshwater temperate ecosystems by integrating data available in the literature. We have four specific objectives: (i) to identify the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 184 publications
1
17
0
Order By: Relevance
“…For freshwater species, we hypothesized that the species richness in the lower HRE would decrease with changed salinity gradients due to spatial avoidance (i.e. ability of organisms to detect and move away from a stressed environment, Venancio et al, 2020;Venancio et al, 2021); while the freshwater species richness in the upper HRE was hypothesized to increase due to displacement of the freshwater species in the lower HRE. To further examine other aspects of species' diversity, we used species evenness which incorporates richness as well as species' abundance for both life stages in upper and lower HRE.…”
Section: Introductionmentioning
confidence: 99%
“…For freshwater species, we hypothesized that the species richness in the lower HRE would decrease with changed salinity gradients due to spatial avoidance (i.e. ability of organisms to detect and move away from a stressed environment, Venancio et al, 2020;Venancio et al, 2021); while the freshwater species richness in the upper HRE was hypothesized to increase due to displacement of the freshwater species in the lower HRE. To further examine other aspects of species' diversity, we used species evenness which incorporates richness as well as species' abundance for both life stages in upper and lower HRE.…”
Section: Introductionmentioning
confidence: 99%
“…Habitat destruction is one of the major threats facing plant species conservation throughout the world. In the Nile Delta, urban crawling and seawater intrusion are the primary threat to the survival of wildlife [1]. When an ecosystem has been dramatically altered by human activities such as agriculture, oil and gas exploration, commercial development, or water diversion it may no longer be able to provide the food, water, cover, and places to raise young that wildlife needs to survive [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The flora of the Nile Delta coastal land is rich in many wild plant species, which seem to be economically promising. The Deltaic Mediterranean coast is distinguished into two divisions: (1) The coastal zone, which can be subdivided into sand dunes, sand flats, salt marshes, and sandy fertile lands; (2) The shorelines of the northeastern corner of Lake Manzala [4]. On the other hand, the cultivated land habitats can be divided into: (1) Winter crops, comprising clover, wheat, broad beans, flax, and winter vegetables; (2) Summer crops, comprising rice, cotton, maize, and summer vegetables; and (3) Orchards, comprising citrus, grapes, and bananas.…”
Section: Introductionmentioning
confidence: 99%
“…How freshwater organisms and ecosystem processes will respond to the increasing salinization of coastal freshwaters, predicted by the Intergovernmental Panel on Climate Change [1], is a fundamental quest for an integrated biodiversity and conservation management of coastal ecosystems at risk. Studies on a wide variety of lakes, rivers, and wetlands have shown salinity effects on freshwater organisms and on ecosystem structure and function [3][4][5][6]. Regarding freshwater animals, salinity may have lethal effects once a threshold is exceeded, or sub-lethal effects, reducing both organism and population fitness, and resulting in the decline of richness with increasing salinity [3,6].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on a wide variety of lakes, rivers, and wetlands have shown salinity effects on freshwater organisms and on ecosystem structure and function [3][4][5][6]. Regarding freshwater animals, salinity may have lethal effects once a threshold is exceeded, or sub-lethal effects, reducing both organism and population fitness, and resulting in the decline of richness with increasing salinity [3,6]. Salinity also affects organisms' spatial distribution, trophic and other interactions, biochemical cycles, and leaf litter decomposition (e.g., [3,[7][8][9]), thus altering ecosystem structure and function.…”
Section: Introductionmentioning
confidence: 99%